Acceptance of e-learning applications by accounting students in an online learning environment at residential universities. (2nd January 2023) - Terblanche, Wendy; Lubbe, Ilse; Papageorgiou, Elmarie; van der Merwe, Nico
Abstract : Technology acceptance models have been used in the higher education context to understand students' acceptance of various learning technologies. Not only was the use of e-learning technologies heightened during the COVID-19 pandemic, but the shift to predominantly online teaching and learning was abrupt. It has become clear that acceptance of e-learning technology will be crucial for higher education in a post-COVID-19 world. Thus, the purpose of this study was to determine the acceptance of e-learning applications by accounting students at residential universities in South Africa. The Unified Theory of Acceptance and Use of Technology (UTAUT2) was adapted for this study to examine the relevance of its constructs in understanding students' intent to use e-learning applications. Accounting students registered at four South African universities completed an electronic questionnaire ( n  = 1 864). Structural Equation Modelling using the Partial Least Squares method was used to test the hypothesised relationships. The findings indicate that performance expectancy, social influence, facilitating conditions, and habit have a significant relationship with behavioural intention to use e-learning applications. However, gender, academic performance, and level of study do not have a significant moderating effect on these relationships. The study reported in this paper contributes to technology acceptance research by testing the UTAUT2 model in a cross-institutional context with a larger sample size than used in similar studies. Furthermore, it has practical value for higher education policymakers, institutions, and lecturers in their attempts to adapt to blended and online learning models.